Profitability of foreign and domestic banks in Central and Eastern Europe: does the mode of entry matter? - Olena Havrylchyk; Emilia Jurzyk (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
Using data for 265 banks in the Central and Eastern European Countries for the period of 1995-2003, this paper analyses the differences in profitability between domestic and foreign banks. We show that foreign banks, especially greenfield institutions, earn higher profits than domestic banks. However, this effect is acquired, rather than inherited, since there is evidence that foreign banks tend to take over less profitable institutions. Profits of foreign banks in the CEEC also exceed profits of their parent banks, explaining the reasons for their entry. Further, we study benefits and costs of foreign ownership by analyzing detfirminants of profitability for domestic, takeover, and greenfield banks. Profits of foreign banks are less affected by macroeconomic conditions in their host countries. However, greenfield banks are sensitive to the situation of their parent banks. Only domestic banks enjoy higher profits in more concentrated banking markets, whereas takeover banks suffer from diseconomies of scale due to the fact that they acquired large institutions.
Keywords: G15; G21; F36; 330; Foreign banks; Bank profits; Multinational banking; Transition economies; Internationale Bank; Internationale Markteintrittsstrategie; Bank; Rentabilität; Schätzung; Osteuropa